Surgical Management of Thoracic Trauma - Suárez, Ivonne Alondra León; Sánchez, Morelos Adolfo García; Alva, María de los Ángeles Carmona; Hernández, José Luis García (British Journal of Healthcare and Medical Research, 2026)
Introduction: Thoracic trauma represents a critical challenge in emergency medicine and trauma surgery, encompassing a broad spectrum of injuries ranging from minor rib fractures to life-threatening visceral damage. Objective: To describe the clinical experience and outcomes of surgical interventions in patients with thoracic trauma treated at public hospitals within the Ministry of Health. Method: A multicenter, retrospective, longitudinal, observational, and descriptive study was conducted by the General Surgery departments of three secondary-care hospitals. Results: The study included 65 patients, all of whom were male (100%), with a mean age of 35 years (mode: 34; range: 20–68). Regarding the mechanism of injury, 96% of cases were attributed to interpersonal violence. The reported morbidity rate was 63.07% (adjusted to 34%), with a mortality rate of 16.6%. Conclusions: In Mexico, surgical thoracic trauma is predominantly associated with interpersonal violence involving male victims. While the diagnosis is frequently evident due to the nature of the presentation, successful management relies heavily on advanced surgical expertise. Surgeons demonstrate high levels of clinical efficiency and technical proficiency in the resolution of these complex cases.